Staging Dystopian Communities: Reimagining Shakespeare in Selected English Plays - Lachman, Michał (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Among the countless afterlives of William Shakespeare’s playwriting there is a strong presence of his visions of state and political powers. In universal, philosophical ways Shakespeare was addressing issues concerning the state power, social organization, hierarchy, and rank in what inevitably were the origins of modern, capitalistic societies. Therefore, many of his powerful images resonate today in the works of contemporary writers who intend to compose stories of utopian or dystopian character which diagnose the condition of modern society. This article aims to present three plays by post-war English dramatists (Edward Bond’s Bingo, Frank McGuinness’s Mutabilitie, and David Greig’s Dunsinane) which reuse Shakespearian themes, motifs, or characters to build politically contentious and subversive plots within a narrower context of their specific cultures, societies, and historical periods. It is assumed that the Shakespearean legacy the writers engage with is not merely a dramatic text, but a complex cultural structure of accumulated narratives, interpretations, and myths which contemporary dramatists rewrite and recycle. The aim of the article is to show how this multifaceted legacy of Shakespeare’s life and work helps build dystopian visions of contemporary communities or images of state and political justice. In other words, the article intends to analyse ways of visualizing modern societies through the palimpsestic presence of the Renaissance master.